2006
DOI: 10.1002/ajmg.a.31124
|View full text |Cite
|
Sign up to set email alerts
|

Systematic search for single nucleotide polymorphisms in a lymphoid tyrosine phosphatase gene (PTPN22): Association between a promoter polymorphism and type 1 diabetes in Asian populations

Abstract: The protein tyrosine phosphatase, nonreceptor 22 gene (PTPN22) maps to human chromosome 1p13.3-p13.1 and encodes an important negative regulator of T-cell activation, lymphoid-specific phosphatase (Lyp). Recently, the minor allele of a single-nucleotide polymorphism (SNP) at nucleotide position 1858 (rs2476601, +1858C > T) was found to be associated with type 1 diabetes. However, the degree of the association is variable among ethnic populations, suggesting the presence of other disease-associated variants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
146
6
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 30 publications
12
146
6
2
Order By: Relevance
“…For example, 73 kb telomeric of rs2476601/Arg620Trp, SNP rs6679677 is in perfect linkage disequilibrium with the PTPN22 functional candidate SNP and genetically and statistically, therefore, is as good a positional candidate as PTPN22 rs2476601/Arg620Trp. Our failure to obtain any evidence for allelic heterogeneity or haplotype effects in type 1 diabetes for this chromosome region suggests that for type 1 diabetes, previous studies (23,25,26) could have been false positives, especially because much smaller sample sizes were studied. We cannot comment on the validity of additional variants in rheumatoid arthritis and Graves' disease (22,24,28), except that any result should be replicated in additional datasets.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, 73 kb telomeric of rs2476601/Arg620Trp, SNP rs6679677 is in perfect linkage disequilibrium with the PTPN22 functional candidate SNP and genetically and statistically, therefore, is as good a positional candidate as PTPN22 rs2476601/Arg620Trp. Our failure to obtain any evidence for allelic heterogeneity or haplotype effects in type 1 diabetes for this chromosome region suggests that for type 1 diabetes, previous studies (23,25,26) could have been false positives, especially because much smaller sample sizes were studied. We cannot comment on the validity of additional variants in rheumatoid arthritis and Graves' disease (22,24,28), except that any result should be replicated in additional datasets.…”
Section: Discussionmentioning
confidence: 63%
“…They identified a rare nsSNP K750N, which generates a premature stop codon, and presented some evidence of association with type 1 diabetes (P ϭ 0.026, minor allele frequency [MAF] ϭ 0.006). An Asian population study (25) did not detect the rs2476601/Arg620Trp variant in 1,690 Japanese or 180 Korean subjects but found a promoter SNP Ϫ1123G/C (rs2488457) to be associated with type 1 diabetes (P ϭ 0.0105; odds ratio (25). Furthermore, a Norwegian rheumatoid arthritis study of 861 case subjects and 559 control subjects (26) found they could not distinguish between Ϫ1123G/C (rs2488457) and rs2476601/Trp 620 because of linkage disequilibrium.…”
mentioning
confidence: 99%
“…Furthermore, Lyp is among the most powerful inhibitors of T cell activation, a task accomplished by dephosphorylation of such molecules. However, we found that this locus was monomorphic in the Japanese population, and that the association was stronger in the promoter SNP than in R620W SNP even in multiplex families of white European origin [67]. These ethnic differences may be associated with susceptibility to or clinical outcomes of type 1 diabetes, and it will be necessary to investigate by biological analysis the mechanisms by which the variants produce disease susceptibility, as well as to investigate the origin of the variants by genetic dissection.…”
Section: Adult Onset Type 1 Diabetesmentioning
confidence: 86%
“…However, the PTPN22 risk allele (R620W) is extremely rare in the Asian population and, so far, there is no evidence of association of PTPN22 with RA in non-White populations (8,9). In contrast, PADI4, SLC22A4, and FCRL3 have been associated with RA in the Japanese population and replicated in the other Asian groups (10)(11)(12), but have given weak or negative results in populations of European ancestry (13,14).…”
Section: Introductionmentioning
confidence: 99%